Growing interest in become a social entrepreneur in youth through waste bank planning - Alwin Ghilman; Deni Abdul Holik; Mira Nurfitriya (Faculty of Economics and Business Mulawarman University, 2023)
This paper aims to find out the interest in social entrepreneurship in adolescents, especially UPI students in the Tasikmalaya area. Using qualitative method with a questionnaire to students of the UPI Kampus Tasikmalaya which was carried out before starting the Garbage Bank business. The emergence of this waste bank initiative is one of the efforts of students to tackle the problem of waste, at least for the campus environment. In addition to making students more concerned about the environment by managing waste, saving waste allows the campus to generate rupiah. However, along the way, there are many waste banks whose sustainability is not clear.